2019
DOI: 10.1111/sode.12359
|View full text |Cite
|
Sign up to set email alerts
|

Physiological contagion in parent–child dyads during an emotional challenge

Abstract: Parents and children mutually influence each other's behavior, but little work has examined how parent-child dyads influence one another's physiological responding under conditions of emotional challenge. This is important to examine because physiological substrates underlie the development of self-regulation. We examined this in 97 parent-child dyads who participated in a frustrating laboratory challenge that first perturbed the affective state of the dyad and then allowed recalibration. Children were between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Second, our approach is also limited by the one-dimensional approach we have taken to studying arousal (STAR Methods; Figure S1). Future work may show discrete patterns of interpersonal influence between parasympathetic and sympathetic subsystems [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Second, our approach is also limited by the one-dimensional approach we have taken to studying arousal (STAR Methods; Figure S1). Future work may show discrete patterns of interpersonal influence between parasympathetic and sympathetic subsystems [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, several studies that use strong multilevel modeling strategies demonstrate that parasympathetic synchrony in toddlerhood is associated with lower maternal and child psychopathological symptoms (Gray et al, 2018; Lunkenheimer et al, 2015 & 2018b, same sample), increased maternal teaching and engagement (Skoranski et al, 2017; same sample as Lunkenheimer et al, 2015; 2018b), and a lack of a history of maltreatment (Creaven et al, 2014). Shih et al (2019) found that parent parasympathetic activity during a frustrating puzzle task positively predicted child parasympathetic activity during recovery, but did not test for associations with behavior or child functioning.…”
Section: Resultsmentioning
confidence: 99%
“…Of the few studies examining sympathetic synchrony during toddlerhood, one small-sample study ( N = 12; Ebisch et al, 2012) used rmANOVA to show increased sympathetic synchrony (nasal-tip thermal imprint) during a distress task compared to baseline, and this was specific to mother–child dyads and not unrelated woman–child dyads (same sample; Manini et al, 2013). Using multilevel modeling techniques with relatively larger sample sizes ( N s = 83–104), others found concurrent PEP or heart rate concordance but no association in change over time (Creaven et al, 2014; Helm et al, 2018; Shih et al, 2019), suggesting this is a between- rather than within-dyad phenomenon. One exception (Laurent et al, 2012, N = 86) found mother–child sAA synchrony during a set of fear- and frustration-eliciting tasks but not during a separation stressor (three saliva samples per task).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, RSA is relevant to everyday interactions in which social engagement and effort are required, including parents’ interactions with their children. Parental emotion and self‐regulation during challenging interactions with young children, who need support and structure during goal‐oriented tasks, correspond with RSA change on the order of seconds wherein greater parenting effort is associated with parent RSA withdrawal (Lunkenheimer et al., 2019; Shih et al., 2019). In laboratory studies, parents show RSA withdrawal when moving from baseline tasks to more effortful tasks (Bornstein & Suess, 2000); parents also show lower RSA concordance with children when that effort is absent, that is, when they are disengaged (Skoranski et al., 2017).…”
Section: Introductionmentioning
confidence: 99%